Observation of SAM-VI Riboswitch Dynamics Using Single-Molecule FRET - Yanyan Xue; Yi Sun; Yichun Xia; Xiuming Liu; Hua Dai (Biomolecules)
Riboswitches regulate gene expression through intricate dynamic conformational transitions, with divalent cation Mg2+ and their ligands playing pivotal roles in this process. The dynamic structural mechanism by which the S-adenosyl-L-methionine (SAM) responsive SAM-VI riboswitch (riboSAM) regulates the downstream SAM synthase gene translation remains unclear. In this study, we employed position-selective labeling of RNA (PLOR) to incorporate Cy3-Cy5 into designated positions of riboSAM, applying single-molecule Förster resonance energy transfer (smFRET) method to track its conformational switches in response to Mg2+ and SAM. smFRET analysis revealed that in the absence of Mg2+ and ligand, riboSAM predominantly adopted a translation-activating apo conformation. Physiological concentrations of Mg2+ induced riboSAM to fold into dynamic transit-p and holo-p states, creating a transient and structurally pliable binding pocket for ligand binding. SAM binding locks the dynamic transit-p and holo-p states into their final stable transit and holo conformations through conformational selection, turning off downstream cis-gene expression and completing feedback regulation of cellular SAM concentration. The observed synergistic regulatory effect of Mg2+ ions and ligand on riboSAM’s conformational dynamics at single-molecule resolution provides new mechanistic insights into gene regulation by diverse riboswitch classes.